Purification of Endogenous Tagged TRAMP4/5 and Exosome Complexes from Yeast and In Vitro Polyadenylation-Exosome Activation Assays - Zigáčková, Dagmar; Rájecká, Veronika; Vaňáčová, Štěpánka (Methods in molecular biology (Clifton, N.J.), 2020)
The RNA exosome processes a wide variety of RNA and mediates RNA maturation, quality control and decay. In marked contrast to its high processivity in vivo, the purified exosome exhibits only weak activity on RNA substrates in vitro. Its activity is regulated by several auxiliary proteins, and protein complexes. In budding yeast, the activity of exosome is enhanced by the polyadenylation complex referred to as TRAMP. TRAMP oligoadenylates precursors and aberrant forms of RNAs to promote their trimming or complete degradation by exosomes. This chapter provides protocols for the purification of TRAMP and exosome complexes from yeast and the in vitro evaluation of exosome activation by the TRAMP complex. The protocols can be used for different purposes, such as the assessment of the role of individual subunits, protein domains or particular mutations in TRAMP-exosome RNA processing in vitro.
Keywords: TAP purification; Mtr4; Air1; Noncanonical poly(A) polymerase; stabilita RNA; Noncoding RNAs; Rrp6; Cell Nucleus; RNA; TRAMP4; Serine Endopeptidases; Saccharomyces cerevisiae - proteiny; Polyadenylation; buněčné jádro; Exosome Multienzyme Ribonuclease Complex; RNA quality control; RNA exosome; Saccharomyces cerevisiae Proteins; exozómy; polyadenylace; serinové endopeptidasy; Trf4; exozom; Air2; Polyadenylation assay; Exosomes; Degradation assay; Saccharomyces cerevisiae; RNA Stability